CDC Group IV c-2: a New Ralstonia Species Close to Ralstonia eutropha - Moissenet, Didier (American Society for Microbiology, 1999)
CDC group IV c-2, an environmental gram-negative bacillus recently proposed for inclusion in the genus Ralstonia, has been isolated in several human infections. Biochemical characterization and 16S ribosomal DNA (rDNA) sequencing with phylogenetic analysis were used to characterize eight clinical isolates and four type strains. Other typing tools, such as pulsed-field gel electrophoresis (PFGE) and randomly amplified polymorphic DNA (RAPD) analysis, were also used. PFGE typing of clinical isolates was unsuccessful because the DNA was degraded, and RAPD analysis was poorly discriminatory. In contrast, the type strains were clearly distinguished with both PFGE and RAPD analysis. All of the 16S rDNA sequences were identical. Comparison of the 16S rDNA sequences to the GenBank sequences showed that they were consistent with CDC group IV c-2 belonging to the genus Ralstonia. The closest matches were obtained with Ralstonia eutropha. However, four differences in 32 biochemical tests separated R. eutropha from CDC group IV c-2, which suggests that CDC group IV c-2 is a new species of the genus Ralstonia.